Role of Probiotics in Pediatric Patients with Helicobacter pylori Infection: A Comprehensive Review of the Literature - Elena Lionetti; Flavia Indrio; Piero Pavone; Giorgia Borrelli; Luciano Cavallo; Ruggiero Francavilla (2010)
Abstract Background: The current guidelines suggest the use of triple therapy as first choice treatment of Helicobacter pylori infection, although the eradication failure rate is more than 30%. Current interest in probiotics as therapeutic agents against H. pylori is stimulated not only by the clinical data showing efficacy of some probiotics in different gastrointestinal diseases but also by the increasing resistance of pathogenic bacteria to antibiotics, thus the interest for alternative therapies is a real actual topic. Aim: To review in vitro and in vivo studies on the role of probiotics in H. pylori infection focusing on the paediatric literature. Materials and methods: Pre‐clinical and clinical paediatric studies in English assessing the role of probiotics in H. pylori infection identified by MEDLINE search (1950–2009) were reviewed. Results: In vitro studies demonstrated an inhibitory activity of probiotics on H. pylori growth and that this effect is extremely strain specific. Available data in children indicate that probiotics seems to be efficacious for the prevention of antibiotic associated side‐effects, and might be of help for the prevention of H. pylori complications by decreasing H. pylori density and gastritis, and for the prevention of H. pylori colonization or re‐infection by inhibiting adhesion to gastric epithelial cells. There is no clear evidence that probiotics may increase the H. pylori eradication rate. Conclusion: Both in vitro and in vivo studies provide evidence that probiotics may represent a novel approach to the management of H. pylori infection.